The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.18097/pbmc20166206674
|View full text |Cite
|
Sign up to set email alerts
|

The hepatic differentiation of adult and fetal liver stromal cells in vitro

Abstract: The liver has a marked capacity for regeneration. In most cases the liver regeneration is determined by hepatocytes. The regenerative capacity of hepatocytes is significantly reduced in acute or chronic damage. In particular, repair mechanisms are not activated in patients with alcoholic cirrhosis. Organ transplantation or advanced methods of regenerative medicine can help such patients. The promising results were obtained in clinical trials involving patients with various forms of liver disease who received t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…For example, Najimi et al [20] found that 99% of liver MSCs were positive for CD90, 92% of the cells were positive for CD73, 88% were positive for CD29, 92% for CD44, and 76% for HLA-Class I. In our work, we showed by flow cytometry that only about 30% of liver MSCs isolated from the liver of patients with cirrhosis and fibrosis expressed CD90 and CD44 [33]. Moreover, a gene expression microarray confirmed that the expression level of CD90 ( THY1 ) was low, while the expression level of CD44 was very high (our unpublished data; see Table 1).…”
Section: Morphology and Phenotype Of Human Liver Mscssupporting
confidence: 49%
See 2 more Smart Citations
“…For example, Najimi et al [20] found that 99% of liver MSCs were positive for CD90, 92% of the cells were positive for CD73, 88% were positive for CD29, 92% for CD44, and 76% for HLA-Class I. In our work, we showed by flow cytometry that only about 30% of liver MSCs isolated from the liver of patients with cirrhosis and fibrosis expressed CD90 and CD44 [33]. Moreover, a gene expression microarray confirmed that the expression level of CD90 ( THY1 ) was low, while the expression level of CD44 was very high (our unpublished data; see Table 1).…”
Section: Morphology and Phenotype Of Human Liver Mscssupporting
confidence: 49%
“…As with MSCs isolated from other sources, liver MSCs do not express markers of hematopoietic and endothelial cells, such as CD11b, CD14, CD19, CD31, CD34, CD45, CD79β, CD117, CD133, CD144, and HLA-DR [20,23,27,33,36]. The lack of expression of CD34, CD45, and CD117 on the surface of liver MSCs suggests that these cells are not so-called hepatic progenitor cells (the human counterpart to rodent oval cells) which are bipotent resident hepatic cells that can differentiate into hepatocytes and cholangiocytes [28,38].…”
Section: Morphology and Phenotype Of Human Liver Mscsmentioning
confidence: 99%
See 1 more Smart Citation
“…The unique features of these cells include immunomodulatory properties and extensive regenerative potential. As shown by several research groups, the liver contains a pool of resident MSCs, which, in terms of their main characteristics (expression patterns of cell surface markers, adhesion, and morphology), correspond to those of MSCs isolated from other tissue sources [12][13][14]. Liver MSCs have several unique characteristics compared with those obtained from other tissue sources.…”
Section: Introductionmentioning
confidence: 99%